Implementation of Grasshopper optimization algorithm based cascaded fuzzy PD-PI controller for frequency stability in a multi-area power system - Tripathy, Debasis; Behera, Sadasiva; Dev Choudhury, N. B. (Journal of interdisciplinary mathematics, 2020)
This article proposed a Grasshopper optimization algorithm (GOA) based cascade controller i.e. fuzzy-PD with PI controller (FPD-PI) for the study of load frequency control. A three unequal-area interconnected power system employed with thermal units has been considered for the present study. Initially, the performance of the GOA technique is verified over the Ant-lion optimization technique with integral square error (ISE) as an objective function. Finally, the supremacy of the proposed FPD-PI controller is verified over other benchmark controllers namely PID and fuzzy-PID with GOA, after ensuring the superiority of integral time multiplied absolute error (ITAE) over ISE.